Low-field electron emission from quatum-size structures of zinc oxide - Gorbik, P. P.; Dadykin, A. A.; Dubrovin, I. V.; Dubrovin, I. V.; Filonenko, M. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
An array of quantum-size zinc oxide structures has been synthesized on semiconductive supports (Si, GaP, GaAs). The field electron emission from quantum-sized zinc oxide was investigated. Eenergetic schemes were suggested of the field emission defined by dimensional quantification in zinc oxide nanostructures.